TRANSITIVITY ANALYSIS OF SYSTEMIC FUNCTIONAL GRAMMAR ON INDONESIAN STATE SPEECH OF JOKO WIDODO - Margaret Stevani; Karisma Erikson Tarigan; Meikardo Samuel Prayuda (Institut Pendidikan Tapanuli Selatan, 2023)
This research aimed to analyze the transitivity in political speech by using systemic functional grammar in each sentence. The data in this research were fragments of clauses which identified the type of transitivity (process, participant, and circumstance), logical meaning, and context of the situation while the source of the data was Jokowi's presidential campaign speech to his volunteer in the 2019 election. This research was carried out using recording and note-taking techniques. The result showed five types of process is used by Joko Widodo, such as material process, relational process, mental process, verbal process, and existential process. The material process in ideational metafunction was the most dominant with the choice of the word